Metal-Catalyzed Multi-Component Approach to Quinoline-Linked Covalent Organic Frameworks - Han, Xianghao; Dong, Shuda; Feng, Xiao (Organic Materials, 2024)
The development of new reaction chemistry is highly desirable to construct new structural and functional covalent organic frameworks (COFs). Benefiting from the extremely large database of metal-catalyzed reaction database, we herein develop a new synthetic strategy that can generate quinoline-linked COFs via a silver-catalyzed three-component one-pot reaction and achieve functionalization by the simple replacement of alcohols. This metal-catalyzed approach to the construction of robust COF structures characterized by extended π-conjugation holds the potential to pave a novel pathway in the synthesis of COF materials endowed with both heightened stability and functionality.
Keywords: covalent organic frameworks; silver-catalyzed; three-component; one-pot; quinoline-linked